Foetal loss and enhanced fertility observed in mice treated with Zidovudine or Nevirapine. - Chika K Onwuamah (PLoS ONE, 2014)
Health concerns for HIV-infected persons on antiretroviral therapy (ART) have moved from morbidity to the challenges of long-term ART. We investigated the effect of Zidovudine or Nevirapine on reproductive capacity across two mouse generations.A prospective mouse study with drugs administered through one spermatogenic cycle. Mouse groups (16 males and 10 females) were given Zidovudine or Nevirapine for 56 days. Males were mated to untreated virgin females to determine dominant lethal effects. Twenty females (10 treated and 10 untreated) mated with the treated males per dose and gave birth to the F1 generation. Parental mice were withdrawn from drugs for one spermatogenic cycle and mated to the same dams to ascertain if effects are reversible. The F1 generation were exposed for another 56 days and mated to produce the F2 generation.Foetal loss was indicated in the dominant lethal assay as early as four weeks into drug administration to the males. At the first mating of the parental generation to produce the F1 generation, births from 10 dams/dose when the 'father-only' was exposed to Zidovudine (10, 100 and 250 mg/kg) was 3, 2 and 1 while it was 7, 1 and 4 respectively when 'both-parents' were exposed. Similarly births from the parental generation first mating when the 'father-only' was exposed to Nevirapine (5, 50 and 150 mg/kg) was 2, 2 and 0 while it was 6, 5 and 9 respectively when 'both-parents' were exposed. However, fertility was not significantly different neither by dose nor by the parental exposure. The F1 mice mated to produce the F2 generation recorded only one birth.The dominant lethal analysis showed foetal loss occurred when the "fathers-only" were treated while fertility was enhanced when "both-parents" were on therapy at the time of mating.